Climate change and health: time for action!. (30th September 2020) - Marrauld, L; Cucchi, M; Lainey, E; Depoux, A
Abstract: Issue: For several weeks, prophylactic messages against the extension of Covid-19 have saturated the public space. To protect populations, efficient measures have been rapidly put to limit the movement of people and manufactured goods. These policies have reduced global greenhouse gas emissions as well as air pollution, especially in China. Problem: If climate change were an epidemic, we would probably have already restored it. But it results directly from the thermo-industrial activities linked to the consumption society. For Friel (Lancet, 2020), the dramatic consequences of this disturbances have to be considered as an essential health issue. She advocates for 'climate change and health alliances'. Results: Within such alliances, health professionals have the responsibility (1) to describe the morbidity inherent in our thermo-industrial societies (2) to alert populations, and (3) to work with allies to tackle climate change and protect human populations, starting with the most vulnerable. This type of alliance is underway in the battle against air pollution, as it has been for years for fighting smoking. Alliances are intended to extend to all population health issues, with a complete decompartmentalization of minds and practices at large scale. Lessons: Health professionals have to be mindful not to cause any harm while practicing. The health system alone produces up to 8% of global greenhouse gas in developed countries (Pichler, 2019; HCWH, 2019). There is room for action. Since 2009, the British health care system (NHS) has adopted an efficient decarbonation policy, reducing global emission from 8 to 4%, but this outstanding initiative remains an exception worldwide. Key messages: A review of public health strategies is necessary to meet the energy, environmental and health issues, both in terms of health risks due to climate change and of decarbonation of care activities. Health professionals have the responsibility to alert populations and to work with allies to tackle climate change and protect human populations.